Role of Cholinergic Anti-Inflammatory Pathway in Protecting Sepsis-Induced Acute Lung Injury through Regulation of the Conventional Dendritic Cells - Ruiting Li; Xuemei Hu; Huibin Chen; Yue Zhao; Xuehui Gao; Yin Yuan; Huiling Guo; Haiyan Huang; Xiaojing Zou; Hong Qi; Hong Liu; You Shang (Hindawi Limited, 2022)
Background. The cholinergic anti-inflammatory pathway connects the immune response system and the nervous system via the vagus nerve. The key regulatory receptor is the α7-subtype of the nicotinic acetylcholine receptor (α7nAChR). Cholinergic anti-inflammatory pathway has been proved to be effective in suppressing the inflammation responses in acute lung injury (ALI). Dendritic cells (DCs), the important antigen-presenting cells, also express the α7nAChR. Past studies have indicated that reducing the quantity of mature conventional DCs and inhibiting the maturation of pulmonary DCs may prove effective for the treatment of ALI. However, the effects of cholinergic anti-inflammatory pathway on maturation, function, and quantity of DCs and conventional DCs in ALI remain unclear. Objective. It was hypothesized that cholinergic anti-inflammatory pathway may inhibit the inflammatory response of ALI by regulating maturation, phenotype, and quantity of DCs and conventional DCs. Methods. GTS-21 (GTS-21 dihydrochloride), an α7nAchR agonist, was prophylactically administered in sepsis-induced ALI mouse model and LPS-primed bone marrow-derived dendritic cells. The effects of GTS-21 were observed with respect to maturation, phenotype, and quantity of DCs, conventional DCs, and conventional DCs2 (type 2 conventional DCs) and the release of DC-related proinflammatory cytokines in vivo and in vitro. Results. The results of the present study revealed that GTS-21 treatment decreased the maturation of DCs and the production of DC-related proinflammatory cytokines in vitro and in sepsis-induced ALI mouse model; it reduced the quantity of CD11c+MHCII+ conventional DCs and CD11c+CD11b+ conventional DCs2 in vivo experiment. Conclusions. Cholinergic anti-inflammatory pathway contributes to the reduction in the inflammatory response in ALI by regulating maturation, phenotype, and quantity of DCs, conventional DCs, and conventional DCs2.